2001
DOI: 10.1002/jbt.1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure‐based studies of cytosolic sulfotransferase

Abstract: Sulfation is a widely observed biological reaction conserved from bacterium to human that plays a key role in various biological processes such as growth, development, and defense against adversities. Deficiencies due to the lack of the ubiquitous sulfate donor 3'-phosphoadenosine-5'-phosphosulfate (PAPS) are lethal in humans. A large group of enzymes called sulfotransferases catalyze the transfer reaction of sulfuryl group of PAPS to the acceptor group of numerous biochemical and xenochemical substrates. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 59 publications
1
54
0
1
Order By: Relevance
“…Both kinetic and crystallographic studies have shown that PAP and PAPS bind at the same binding site in each SULT (Yoshinari et al, 2001;Chapman et al, 2004;Wang and James, 2006), and we determined binding at this site by titration with PAP. These studies were conducted in 0.25 M potassium phosphate, pH 7.4, with an excitation wavelength of 290 nm and an emission wavelength of 347 nm (entrance and the exit slits were set at 5 and 7 nm, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Both kinetic and crystallographic studies have shown that PAP and PAPS bind at the same binding site in each SULT (Yoshinari et al, 2001;Chapman et al, 2004;Wang and James, 2006), and we determined binding at this site by titration with PAP. These studies were conducted in 0.25 M potassium phosphate, pH 7.4, with an excitation wavelength of 290 nm and an emission wavelength of 347 nm (entrance and the exit slits were set at 5 and 7 nm, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The three cytosolic SULT structures are highly conserved, and a number of key features of the SULT active site and reaction mechanism (reviewed in 36 ) can be deduced from these and other studies (see Figure 2). The amino acids involved in binding the sulfuryl donor PAPS are, as would be expected, highly conserved throughout the SULT family.…”
Section: Structure-function Studies On Sulfotransferasesmentioning
confidence: 95%
“…Dashed lines outline the extended amino-and carboxy-terminal ends of SULT2B1a and SULT2B1b. Boxed residues delineate conserved amino acids involved in 5Ј-phosphoadenosine-3Ј-phosphosulfate cofactor interaction (129,130). Multiple alignment analysis was carried out using the MacVector 7.0 system, which is based on the Clustal W algorithm (131).…”
Section: Cholesterol Sulfotransferasesmentioning
confidence: 99%